Perbedaan Hasil Belajar Pada Materi Tumbuhan Lumut Melalui Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share dan Think Pair Square Siswa Kelas X SMA Negeri 4 Banda Aceh - E, Erlita; Yunanda, Novia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Research on Differences of Learning Outcomes moss plants Through Application Model Cooperative Learning Think Pair Share and Think Pair Square at Class X SMAN 4 Banda Aceh.The purpose of this study was to determine whether there is any difference in the implementation of cooperative learning model Think Pair Share and type of Think Pair Square on learning outcomes physics class students on the concept of Fluid Static X SMAN 4 Banda Aceh.The method used is a quasi-experimental research method (Quasi Experimental).This study population dalah whole graders X.IA SMAN 4 Banda Aceh.As for determining the sample use a sampling technique of non-probability sampling with purposive sampling technique.Thus, the samples of this research is class X.IA 5 totaling 30 people (experimental class 1) and class X.IA 2 totaling 30 people (the experimental class 2).Data collected through documentation and testing. Data were analyzed using t-test statistic to test for differences in learning outcomes. Based on the analysis of data obtained t table = -0.55 2,002then Ho is accepted.It can be concluded that there is no difference between the use of learning outcomes learning model Think Pair Share with learning model Think Pair Square in physics concepts in the classroom moss plants X SMAN 4 Banda Aceh the school year 2024/2025.